Genetic Gestational Surrogacy: Hope for Muslims - Lasker, shamima Parvin; Ghilardi, Marcello (Bangladesh Journal of Bioethics, 2017)
More than half a million couples may be suffering from infertility in the world. When in vitro fertilization is unsuccessful, surrogacy may be a substitute choice for many couples. Literature shows that ten million Muslims are infertile worldwide. According to Islamic theology the concept of surrogacy is null and void as formation of blastocyst constitutes from sperm that is transferred to the uterus of a woman who is not married to him. In Islam, marriage is the only legal procedure to procreation for preservation of lineage, inheritance, prevention of adultery and prevention of possibility of incest among the half-siblings.  Genetic gestational surrogacy (sperm of husband and ovum of wife is fertilized by IVF procedure and transfer the embryos to the surrogate mother) may be free from social, legal and moral complications. Some Islamic countries have reluctant law in favour of surrogacy, as for example Iran, Lebanon and sporadic parts of the Muslim world. This article has attempted to find out a valid notion for accepting genetic gestational surrogacy in major part of the Muslim world that may reduce the peril of women who can not give a birth baby.